News and policy foresight in a macro-finance model of the US - Cristian Badarinza; Emil Margaritov (European Central Bank (ECB), 2011)
We study the effects of information shocks on macroeconomic and term structure dynamics in an estimated medium-scale DSGE model for the US economy. We consider news about total factor productivity and investment-specific technology, as well as foresight about monetary policy. Our empirical investigation confirms the findings of previous studies on the limited role played by productivity news in this class of models. In contrast, we uncover a non-trivial role for investment-specific news and anticipated monetary policy shocks not only in the historical and variance decomposition of real economic variables but also for the overall dynamic behavior of the term structure of interest rates. We also document substantial qualitative differences in the dynamic responses of the macroeconomy and the bond yield term structure to anticipated and surprise structural and policy innovations.
Keywords: E32; E43; E52; 330; DSGE model; news; Policy Foresight; Term structure